The Effects of Papaya Leaf Extract and Turmeric Extract Inclusion on Total Apparent Digestibility of Nutrients and Methane Gas Production in Bali Cattle - Nurmeiliasari Nurmeiliasari; N. J. Rangkuti; H. D. Putranto; E. Yunita; J. Firison; H. Kusnadi (Jurnal Sain Peternakan Indonesia, 2023)
This research evaluated the effects of papaya leaf and turmeric extract supplementation on the total apparent digestibility of nutrients and methane gas production in Bali cattle. The livestock used were 18 Bali cattle that were distributed into treatment without papaya leaf and turmeric extract supplementation (P0),  Supplementation of 0.0075% turmeric extract g/kg live weight/day (P1), and supplementation of 0.00375% turmeric extract per kg live weight per day + 0.00375% papaya leaf extract per kg live weight per day (P2). The basal diets were 60% elephant grass cv. Taiwan (Pennisetum purpureum cv. Taiwan) and 40% concentrate. The ration provision was three per cent dry matter of body weight. The observed parameters included feed consumption, feces production, dry matter digestibility, organic matter digestibility, crude protein digestibility, crude fat digestibility, crude fibre digestibility, nitrogen-free extract digestibility, and methane gas production. The research results indicated that the treatment did not significantly affect feed consumption (P>0.05) but did affect crude protein digestibility, crude fibre digestibility, nitrogen-free extract digestibility, and methane gas production. This study concludes that the feeding of elephant grass cv. Taiwan (Pennisetum purpureum cv. Taiwan), with the addition of papaya leaf extract and turmeric extract, does not have a positive effect on feed consumption and feed digestibility; thus, it cannot suppress methane gas production in livestock.